A Review of an In-depth Interview on Urban Planning and Development - Lamsal, Parshuram; Adhikari, Anup; Aryal, Vijay; Aryal, Bhagwan (Molung Educational Frontier, 2025)
An in-depth interview is an effective and widely employed tool in qualitative research for collecting information. The research used an in-depth interview on urban planning and development. Different journal articles were thoroughly studied, and new knowledge was found. In-depth interview methodology was reviewed and applied in the context of data collection for urban planning and development. Urban planning is relevant today as people swiftly transition from rural to urban areas to meet their growing needs. In-depth interviews are a crucial method in urban studies, providing valuable insights into the lived experiences of residents and the impact of urban planning. These interviews allow in-depth exploration of complex issues while considering ethical guidelines and rigorous data analysis. Though time-consuming and costly, they offer rich data for descriptive research across various fields, contributing significantly to the advancement of urban research. However, there is a lack of essential infrastructure, i.e., transportation, which may limit the generalizability of its findings to other areas. Due to a lack of skilled interviewers and interview materials, as well as location and favourable time constraints, participants may not be ready to discuss sensitive ethical issues. This approach proves highly effective in uncovering valuable data. Thematic analysis organized all significant qualitative research findings into valuable and insightful themes for future urban planning and development research.